The Automation Of Robotic Processes In Jordanian Banks: Obstacles And Applications - Abedalfattah Zuhair Al-abedallat; Ali Bakhit Jaafreh; Duraid Kamel Alshbib (European Scientific Journal, ESJ, 2021)
Abstract This paper focuses on identifying the impact of technical and financial obstacles to the applications and expansion of the smart branches of banks in Jordan. This, however, depends on the Automation of Robotic Processes to identify the reality of applying smart branches in the world, including Jordan. The study employed a sample of 100 employees selected in an equal random manner from 25 Jordanian banks. With its spreading strands, multiple linear regression was used to test the hypotheses of the study. The study concluded that the expansion of banks of smart branches (robots) contributes to reducing operational cost and increasing the bank's profits by reducing the cost of banking service, enhancing its quality, increasing the market share of banks, and reducing the technical and financial obstacles that have a significant impact on the expansion of the smart branches of banks. The study recommended the importance of the development of smart branches of banks in Jordan due to its benefits in reducing the costs of the provided banking service. This contributes to increasing its profits. Also, banks should hold specialized training courses for bank workers on how to use the new technology. Banks should also allocate funds needed to create the essential infrastructure for the smart branch Applications of Artificial Intelligence, as this has an impact in achieving competitive advantage.